Efektivitas Penggunaan Media Roda Putar pada Pembelajaran IPS Peserta Didik Kelas VII SMP Islam MAN Baul Ulum Mayong Jepara - Istifadah, Kholis; Nisa, Aisyah Nur Sayidatun (Sosiolium: Jurnal Pembelajaran IPS, 2021)
Education that is able to produce good citizens is education that is able to develop student potential, so that they are able to face the life problems they face. The use of learning resources and learning methods that are less varied and monotonous can cause boredom in students because they are not directly involved in the teaching and learning process, as a result the learning material is not fully accepted by students, in carrying out the objectives of social studies there are still some obstacles in school, namely less active students in receiving social studies learning, as well as not optimally utilized models or media and lack of adequate facilities and infrastructure. The problems above can be overcome by the need for teacher creativity in the use of learning methods, models and resources to support the learning process. The purpose of this study was to determine the effectiveness of social studies learning using the class VII F rotating wheel of SMP Islam Manba'ul Ulum Jepara.